The Effect of Profitability, Solvency, and Liquidity on Dividend Policy with Market Ratios as a Moderating Variable in Energy and Basic Materials Sector Companies Listed in the Kompas100 Index During the 2019–2024 Period - Halim, Jevon Edbert Baruch; Nisa, Chaerani (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to analyze the factors that affect dividend policy in companies in the energy and basic materials sectors listed in the Kompas100 Index. The independent variables used are profitability, solvency, and liquidity, while the dependent variables are dividend policy, and the moderation variable is market ratio. This study uses a quantitative approach with 5 samples of companies in the energy and basic materials sectors listed in the Kompas100 Index for the 2019-2024 period. The sampling technique uses purposive sampling. This research uses secondary data, namely the company's annual financial statement data. The analysis method used was multiple regression analysis using Eviews12. The results of the study show that profitability, solvency, and liquidity both partially and simultaneously do not have a significant effect on dividend policy. In addition, the market ratio variable is not able to moderate the relationship between independent variables and dependent variables.